Strengthening MSMEs through Business Management and Accounting to Enhance Competitiveness: A Community-Based Approach in Meranjat 3 Village, Ogan Ilir - Eni Cahyani; Maftuhah Nurrahmi; Zaleha Trihandayani; Nurul H. Ningsih; Fenty Asterina; Mia Kusumawaty; Kurnia K. Sari; Fitantina (IJECS: Indonesian Journal of Empowerment and Community Services, 2026)
ABSTRACT This community service activity is aimed at Micro, Small, and Medium Enterprises (MSMEs) in Meranjat 3 Village, Ogan Ilir Regency. The program involves students participating in the Community Service Program (KKN), supervised by field supervisors (DPL) and lecturers from the Faculty of Economics and Business, to address existing challenges. The main problems identified include the low level of business legality, with more than 90% of MSMEs still operating as informal micro-enterprises without legal status. In addition, many MSME actors still rely on conventional business practices, despite the ongoing push toward digital entrepreneurship transformation. Furthermore, less than 10% of MSMEs have established partnerships with larger companies, often due to limited access to information. Based on these issues, the program focuses on strengthening MSMEs through business management and accounting. The activity is conducted in the form of workshops aimed at enhancing the knowledge and understanding of MSME actors regarding the identified challenges.   Keywords: Micro, Small, and Medium Enterprises (MSMEs), Business Management, HPP